Diving beneath the sea of stellar activity: chromatic radial velocities of the young AU mic planetary system - Cale, Bryson; Reefe, Michael; Plavchan, Peter; Tanner, Angelle; Gaidos, Eric; Gagné, Jonathan; Gao, Peter; Kane, Stephen R.; Béjar, Víctor J. S.; Lodieu, Nicolas; Anglada-Escudé, Guillem; Ribas, Ignasi; et al. (The astronomical journal, 2021)
We present updated radial-velocity (RV) analyses of the AU Mic system. AU Mic is a young (22 Myr) early-M dwarf known to host two transiting planets—P b ∼ 8.46 days, , P c ∼ 18.86 days, . With visible RVs from Calar Alto high-Resolution search for M dwarfs with Exo-earths with Near-infrared and optical echelle Spectrographs (CARMENES)-VIS, CHIRON, HARPS, HIRES, Minerva-Australis, and Tillinghast Reflector Echelle Spectrograph, as well as near-infrared (NIR) RVs from CARMENES-NIR, CSHELL, IRD, iSHELL, NIRSPEC, and SPIRou, we provide a 5σ upper limit to the mass of AU Mic c of M c ≤ 20.13 M ⊕ and present a refined mass of AU Mic b of . Used in our analyses is a new RV modeling toolkit to exploit the wavelength dependence of stellar activity present in our RVs via wavelength-dependent Gaussian processes. By obtaining near-simultaneous visible and near-infrared RVs, we also compute the temporal evolution of RV “color” and introduce a regressional method to aid in isolating Keplerian from stellar activity signals when modeling RVs in future works. Using a multiwavelength Gaussian process model, we demonstrate the ability to recover injected planets at 5σ significance with semi-amplitudes down to ≈10 m s−1 with a known ephemeris, more than an order of magnitude below the stellar activity amplitude. However, we find that the accuracy of the recovered semi-amplitudes is ∼50% for such signals with our model.